Main currents of Marxism : its origins,growth and dissolution. - Kołakowski, Leszek (Oxford University Press, 2005)
"Drawing on powerful historical and philosophical insight, Main Currents of Marxism traces the intellectual foundations of Marxist thought from Plotinus through Hegel to Lukacs, Sartre, and Mao. Leszek Kolakowski reveals Marxism to be "the greatest fantasy of our century ... an idea that began in Promethean humanism and culminated in the monstrous tyranny of Stalinism." Long before the overwhelming majority of historians, journalists, and intellectuals around the world came to see the devastation wrought by autocratic, state-sponsored socialism, Kolakowski pointed to the shortcomings of a system doomed to failure." "Recognized when it was first published for its profound historical insights and for its exposition of how the Communist hierarchy was quickly corroding from the inside, this forceful work has influenced several generations of scholars and historians. Despite decades of major political change, Main Currents of Marxism remains as accurate and incisive as ever. In a new preface and epilogue, Kolakowski reexamines the collapse of international Communism in light of the last tumultuous years."--BOOK JACKET.